2009
DOI: 10.3329/bjp.v4i2.2488
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the antidiabetic effects of Mangifera indica stem-barks and leaves on nondiabetic, type 1 and type 2 diabetic model rats

Abstract: Studies on the antidiabetic effects of Mangifera indica stem-barks and leaves on nondiabetic, type 1 and type 2 diabetic model rats. Bangladesh J Pharmacol. 2009; 4: 110-14. AbstractMangifera indica Linn, locally known as mango tree has been claimed to possess antidiabetic properties by many investigators. The present study was undertaken to screen the hypoglycemic and antihyperglycemic activity of both ethanol and water extracts of leaves and stem-barks of M. indica in nondiabetic and diabetic model rats in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 10 publications
3
34
0
Order By: Relevance
“…DM, characterized as genetically based predisposition and dietary indiscretion [2] is ranked seventh among the leading causes of death and third when it's fatal complications are taken into account [3,4]. There is increasing evidence that complications related to diabetes like retinopathy, atherosclerotic vascular disease are associated with oxidative stress induced by the generation of free radicals [5].…”
Section: Introductionmentioning
confidence: 99%
“…DM, characterized as genetically based predisposition and dietary indiscretion [2] is ranked seventh among the leading causes of death and third when it's fatal complications are taken into account [3,4]. There is increasing evidence that complications related to diabetes like retinopathy, atherosclerotic vascular disease are associated with oxidative stress induced by the generation of free radicals [5].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic mellitus (DM) is ranked seventh among the leading causes of death and third when its fatal complications are taken into account [1]. Within the human body the pancreas controls blood glucose by producing and releasing the hormones insulin and glucagon, which stabilize blood glucose within the physiological range of 70-120 mg/ dl.…”
Section: Introductionmentioning
confidence: 99%
“…The intestinal disaccharidase enzymes ( -glucosidase) are involved in the digestion and absorption of carbohydrate and inhibition of these enzymes by the agents may slow this process and thus leads to a slower and less pronounced rise in postprandial blood glucose levels. It has been confirmed that some plant fractions i.e hot water extract extract of T foenumgraecum P. ovata and ethanol extracts of O sanctum, A racemosus, M indica (Bhowmik 2009), T indica (not published) significantly inhibited the absorption of glucose during perfusion of gut with glucose solution, a mechanism postulated before through in vivo experiments. T foenumgraecum (Hannan, et.al., 2003(Hannan, et.al., & 2007a , P. ovata (Hannan, et.al., 2006a) O sanctum (Hannan, et.al., 2006b) and A racemosus, (Hannan, et.al., 2007b) increased unabsorbed sucrose content throughout gut when administered with sucrose and also inhibitited intestinal disaccharidase enzyme activity, which reveals that the retardation of carbohydrate absorption is related to the inhibition of gut enzyme activity.…”
Section: Studies On the Retardation Of Glucose Absorption In The Gutmentioning
confidence: 70%
“…Enhance or promote insulin secretion Momordica charantia (Ali et al, 1993) Costus speciosus (Mosihuzzaman et al, 1994) Coccinia indica Premna integrifolia Linn (Alamgir et al, 2000) Spirulina platensis (Rokeya et al, 1999) Bridelia ndellensis (Soheng et al, 2005) Nephrolepsis tuberosa (Mosihuzzaman et al, 1994) Swetenia mahagoni Pterospermum semisagittum 2. Inhibition of glucose absorption Trigonella foenum graceum (Ali et al, 1995 Syzgium cumini (Rokeya et al, 1999) Plantago ovata (Rokeya et al, 1999) Musa paradisiaca Allium cepa (Rokeya et al, 1999) Pterospermum acerifolium (Mamun et al, 2001) Allium sativum (Rokeya et al, 1999& Retal et al, 1999 Costus Specious (Mosihuzzaman et al, 1994) Allium Wallicha Spirulina platensis (Rokeya et al, 1999) Asparagus racemosus (Hannan et al, 2007) Crateava Religiosa Ocimum sanctum (Alamgir et al, 2000) Mangifera indica (Bhowmik et al, 2009) Ipomoea aquatica (Sokeng et al, 2007) Tamarindus indicus 3. Action on the peripheral tissues Coccinia indica Nephrolepsis tuberosa (Mosihuzzaman et al, 1994) Costus speciosus (Mosihuzzaman et al, 1994) 4.…”
Section: Research Work On Antidiabetic Plant Materials Done By the Dhmentioning
confidence: 99%